Role of social support in the relationship between resilience and sleep quality among cancer patients - Cui, ChunYing; Wang, Lie (Frontiers in Psychiatry, 2024)
Introduction The present study aimed to investigate the effect of resilience on sleep quality and explore the role of social support between resilience and sleep quality in cancer patients. Methods A multicenter and cross-sectional study was conducted in China from May to November 2021. A total of 202 cancer patients were recruited to complete the questionnaires composed of demographic information, Pittsburg Sleep Quality Index (PSQI), Resilience Scale-14 (RS-14), and Multidimensions Scale of Perceived Social Support (MSPSS). The associations between resilience, social support, and sleep quality were explored through hierarchical regression analysis. Results The prevalence of poor sleep quality was 50% among cancer patients. Resilience, social support, and the interaction between resilience and social support were all found to be significantly associated with sleep quality. Results of simple slope analysis indicated that the association between resilience and sleep quality were gradually decreased with the increasing social support levels (1 SD below the mean, B=-0.225, β=-0.551, P<0.001), mean social support (B=-0.147, β=-0.353, P<0.001) and high social support (1 SD above the mean, B=-0.065, β=-0.156, P<0.001). Additionally, social support mediated the effect of resilience on sleep quality among cancer patients. Discussion Poor sleep quality has been common in cancer patients. Social support could mediate and alleviate the relationship between resilience and sleep quality among cancer patients. Besides providing sufficient social support, interventions based on resilience should be applied to address sleep problems in cancer patients.